Beta version!

A particle moves in a straight line whose acceleration a a depends on the velocity v v according to the equation a = α v a=-\alpha\sqrt{v} , where α \alpha is a positive constant.

At the initial moment, the velocity of the particle is v 0 {v}_{0} .

If the average speed just before it stops is v 0 β \large{\frac{{v}_{0}}{\beta}} , where β \beta is a positive integer , find β \beta .


The answer is 3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Vaibhav Prasad
May 21, 2016

For average speed, we need total distance x x and total time t t .

a = α v d v d t = α v 1 v d v = α d t v 0 0 1 v d v = α 0 t d t 2 v 0 = α t 2 v 0 = α t t = 2 v 0 α \large{a=-\alpha \sqrt { v } \\ \frac { dv }{ dt } =-\alpha \sqrt { v } \\ \frac { 1 }{ \sqrt { v } } dv=-\alpha dt\\ \int _{ { v }_{ 0 } }^{ 0 }{ \frac { 1 }{ \sqrt { v } } dv=-\alpha \int _{ 0 }^{ t }{ dt } } \\ -2\sqrt { { v }_{ 0 } } =-\alpha t\\ 2\sqrt { { v }_{ 0 } } =\alpha t\\ \boxed{t=\frac { 2\sqrt { { v }_{ 0 } } }{ \alpha }} }

Also,

a = α v d v d t = α v d v d t d x d x = α v ( d x d t ) d v d x = α v v d v d x = α v v d v = α d x v 0 0 v d v = α 0 x d x 2 3 ( v 0 ) 3 2 = α x 2 3 ( v 0 ) 3 2 = α x x = 2 3 ( v 0 ) 3 2 α \large{a=-\alpha \sqrt { v } \\ \frac { dv }{ dt } =-\alpha \sqrt { v } \\ \frac { dv }{ dt } \cdot \frac { dx }{ dx } =-\alpha \sqrt { v } \\ \left( \frac { dx }{ dt } \right) \cdot \frac { dv }{ dx } =-\alpha \sqrt { v } \\ v\cdot \frac { dv }{ dx } =-\alpha \sqrt { v } \\ \sqrt { v } dv=-\alpha dx\\ \int _{ { v }_{ 0 } }^{ 0 }{ \sqrt { v } dv=-\alpha \int _{ 0 }^{ x }{ dx } } \\ -\frac { 2 }{ 3 } { \left( { v }_{ 0 } \right) }^{ \frac { 3 }{ 2 } }=-\alpha x\\ \frac { 2 }{ 3 } { \left( { v }_{ 0 } \right) }^{ \frac { 3 }{ 2 } }=\alpha x\\ \boxed{x=\frac { \frac { 2 }{ 3 } { \left( { v }_{ 0 } \right) }^{ \frac { 3 }{ 2 } } }{ \alpha }}}

Finally, x t = v 0 3 \large {\frac{x}{t}=\frac{{v}_{0}}{3}} . Hence β = 3 \beta =\boxed{\large{3}}

Nice one...

Sparsh Sarode - 5 years ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...